A Best Practice Model of Harm Reduction in the Community and in Prisons in the Russian Federation - Burrows, Dave (2013)
The Final Project Report is the result of a study commissioned by the World Bank in 2001 to examine best practice harm reduction for HIV prevention among injecting drug users (IDUs) in community and prison settings in the Russian Federation. The report is based on 26 surveys completed by needle and syringe exchange projects (NSEPs) in the Russian Federation, interviews with NSEP staff and key informants, and other research. Main strengths of programs were considered to be: support from local authorities and institutions; caring attitude and pragmatic approach of NSEPs; international technical support and funding and peer education. Weaknesses cited included: insufficient funds to meet needs; low reach; management problems; patchy quality of services. The project finds that there needs to be educational materials tailored to the needs of staff and prisoners, provision of peer education programs, and linkage between prisons and community programs. This paper summarizes results of the research and provides recommendations for best practice for harm reduction.